Penerapan Standar Nasional Indonesia Produk Beras Yang Beredar Pada Masyarakat Dalam Perspektif Perlindungan Konsumen - Isis Ikhwansyah; Resmaya Agnesia Mutiara Sirait (Magister Kenotariatan, Universitas Jambi, 2020)
As the main staple, rice becomes a food that must have good quality and is safe for consumption. The Indonesian National Standard is a parameter used as a benchmark for the feasibility of a product being circulated, so that the application of the Indonesian National Standard on rice products is needed to protect the security and safety of consumers. The irony is that this has not yet become the awareness of the business actors. To protect consumers from loss requires legal measures that consumers can do in accordance with consumer protection laws. As for the problems are: the application of good Indonesian National Standards regulations on rice products circulating in traditional and modern markets in Indonesia, and legal remedies carried out by consumers who suffer losses on rice products circulating on the market in Indonesia. The results of the research show that the application of SNI regulations is good to be applied to rice products circulating in modern markets and traditional markets in Indonesia, through the application of SNI rice where the regulations are not in accordance with the principles contained in the UUPK. Good legal remedies to be carried out by consumers who suffer losses on rice products circulating in the Indonesian market are certainly through consumer dispute resolution outside the court, namely through the Consumer Dispute Resolution Agency which acts as an intermediary in resolving disputes.